1987
DOI: 10.1111/j.1365-2621.1987.tb00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oil uptake and moisture loss during frying of potato slices from c. v. Record U.K. tubers

Abstract: The variations in moisture content and oil content of samples of 1.5-mm thick slices of potato (c.v. Record U.K.) were examined after various frying times at frying temperatures of 145, 165 and 185°C. The loss of moisture and the uptake of oil were found to be interrelated and both were linear functions of the square root of frying time. Within the temperature range examined, moisture loss and oil uptake were found to be independent of frying temperature. From the data and visual observations the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
2
10

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(141 citation statements)
references
References 4 publications
13
111
2
10
Order By: Relevance
“…The final oil content of the dough (with emulsifier) was found to be comparable to that of the potato sample. This is in agreement with [3,8,13,17,23,28,32,34] , who also reported the barrier effect which a crust has on oil uptake.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The final oil content of the dough (with emulsifier) was found to be comparable to that of the potato sample. This is in agreement with [3,8,13,17,23,28,32,34] , who also reported the barrier effect which a crust has on oil uptake.…”
Section: Discussionsupporting
confidence: 82%
“…This result is in agreement with Gamble et al [13,14] and Moreira et al [24] who studied the effect of different frying temperatures on potato crisps, tortilla chips, plantain slice and plantain slices, respectively. The former found that although the early stages of frying showed the lower oil temperature resulted in lower oil content, but the overall oil content is temperature independent within the oil temperature examined.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Oleh itu, keupayaan menghalang kelembapan salutan filem menurun. Gambel et al (1987) melaporkan bahawa semasa penggorengan, jumlah minyak yang masuk ke dalam sampel adalah berkadar dengan jumlah kehilangan air daripada sampel tersebut. Minyak akan menggantikan ruang-ruang yang ditinggalkan oleh air.…”
Section: Kandungan Kelembapanunclassified
“…Researches on heat and mass transfer of vacuum frying process were still very limited. Most of the researches on mass and heat transfer were dealing with immersion frying [5,6], pan frying, and deep fat frying [7][8][9][10] or baking [11]. These technologies have caused considerable amount of functional properties of the fresh foods.…”
Section: Introduction mentioning
confidence: 99%